The tiles installer robot / Mohammad Syamim Zikrie Mat Zakie and Mohamad Hamdan Othman - Mat Zakie, Mohammad Syamim Zikrie; Othman, Mohamad Hamdan (2024)
This comprehensive study delves into the Tiles Installer Robot, highlighting its inception, progression, and integration into the construction field. The methodology employed involves rigorous experimentation, wherein the robot's efficiency and precision in tile installation undergo meticulous evaluation within a controlled setting. Our design framework incorporates features aimed at enhancing problem-solving capabilities and providing factual visualizations aligned with predefined research parameters. Extensive desk research provides invaluable insights into public perception, practical applications, pricing structures, capabilities, and commercial availability. Advancing the Tiles Installer Robot relies heavily on the meticulous analysis of data, which illuminates technological intricacies, installation process efficacy, and the robot's adaptability to diverse environments. The design study meticulously examines the conceptual underpinnings of the project, encompassing structural components, navigation techniques, tile installation methodologies, and the utilization of simulations to gauge performance across various scenarios. The design carefully integrates ergonomics and user interface considerations, resulting in a solution that aligns seamlessly with project objectives. Domain specialists collaboratively crafted this avant-garde solution, meticulously detailing it within the report's chapters. The research findings not only enrich the burgeoning realm of robotic technologies in construction but also underscore the paramount importance of innovative design and evidence-based decision-making in fostering excellence in construction robotics.